Managing dengue disaster: uncovering paramount community elements for DNA sensory tool accessibility in Malaysia - Nur-Fadhilah Mazlan; Tan, Ling Ling; Mohammad Imam Hasan Reza; Goh, Choo Ta; Nurul Huda Abd. Karim; Lee, Yook Heng (Penerbit Universiti Kebangsaan Malaysia, 2020)
In this study, communities’ psychosocial judgements (relationship, awareness, responsibility, and attitude) were evaluated in relation to DNA-based dengue kit accessibility. It was carried out by handing out 100 structured questionnaires (Kajang Housing (KjH): 40, Kajang Industrial (KjI): 40, Kuala Selangor (KuS): 20). From our descriptive analyses, KuS respondents exhibited a closer relationship with their neighbours (100%) compared to other respondents. KjH, KjI and KuS respondents know very little about dengue vector species. While KjH is leading the other two study areas, KjI and KuS in terms of knowing all symptoms associated with dengue fever (DF), KuS shows more interest to participate in dengue campaigns and/or prevention and control programs compared to KjH and KjI. Not more than 25% of total respondents are willing to offer transportation or nurturing their neighbours back to health. While KjI is more confident to use DNA biosensor when outside of their community, not more than 35% of total respondents are confident enough to use it within their neighbourhood. All communities, especially the affected ones, should take a proactive step by making use of DNA biosensor as an early warning tool, in conjunction with good psychosocial behaviours towards dengue, to achieve sustainable health promotion in managing dengue disaster.